TLR3 Regulated Poly I:C-Induced Neutrophil Extracellular Traps and Acute Lung Injury Partly Through p38 MAP Kinase - Gan, Tingting; Yang, Yonglin; Hu, Fan; Chen, Xichen; Zhou, Jiawei; Li, Yan; Xu, Ying; Wang, Huijuan; Chen, Yu; Zhang, Mingshun (Frontiers in Microbiology, 2018)
Acute lung injury (ALI) is the leading cause of morbidity and mortality in critically ill patients. Neutrophil extracellular traps (NETs) have been well documented in the ALI model of bacterial infection. In the present study, we demonstrated that poly I:C could induce pulmonary NETs. Upon poly I:C intratracheal inoculation, neutrophil infiltration in the bronchoalveolar lavage fluid (BALF) was significantly increased. Furthermore, the inflammatory cytokines IL-1β, IL-6 and TNF-α in the lung were also significantly elevated. Neutrophil depletion abolished NETs and decreased both neutrophil infiltration and IL-1β in the lung. As expected, DNase I, an inhibitor of MPO and NADPH, decreased pulmonary inflammation and NETs. Blocking of the poly I:C receptor TLR3 reduced lung inflammation and NETs. The MAPK kinase inhibitor p38 diminished the formation of NETs and restored the expression of the tight junction protein claudin-5 in the mouse lung when challenged with poly I:C. In summary, poly I:C induced the formation of pulmonary NETs and ALI, which may be associated with the activation of p38 MAPK and the decreased expression of claudin-5.